2020
DOI: 10.1002/ange.202012059
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Anatomy of Iron‐Silica Self‐Organized Membranes: Implications for Prebiotic Chemistry

Abstract: Iron-silica self-organized membranes,s o-called chemical gardens, behave as fuel cells and catalyze the formation of amino/carboxylic acids and RNAn ucleobases from organics that were available on early Earth. Despite their relevance for prebiotic chemistry,l ittle is knowna bout their structure and mineralogy at the nanoscale.S tudied here are focused ion beam milled sections of iron-silica membranes, grown from synthetic and natural, alkaline,s erpentinizationderived fluids thought to be widespread on early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 86 publications
(157 reference statements)
0
9
0
Order By: Relevance
“…[25] Though it is thought that iron-silicate chemical gardens contain iron oxyhydroxides, these minerals are proposed to be present mainly on the inner layers of the structure, with a silica layer on the outside. [17,22] Previous prebiotic chemistry studies with iron-silicate chemical gardens observed different suites of organic products in the interior of the chemical garden than in the outer silicate solution. [16] The membrane itself is expected to have a significantly higher reactivity in comparison to that of the silicate in solution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[25] Though it is thought that iron-silicate chemical gardens contain iron oxyhydroxides, these minerals are proposed to be present mainly on the inner layers of the structure, with a silica layer on the outside. [17,22] Previous prebiotic chemistry studies with iron-silicate chemical gardens observed different suites of organic products in the interior of the chemical garden than in the outer silicate solution. [16] The membrane itself is expected to have a significantly higher reactivity in comparison to that of the silicate in solution.…”
Section: Resultsmentioning
confidence: 99%
“…[8,[18][19][20][21] Chemical garden precipitates in the ferrous chloride/ sodium silicate reaction system exhibit a bilayer structure, and are composed of amorphous silica and iron oxyhydroxides. [22] Notably, chemical gardens have been found to have highly reactive nanostructural properties. [22] The specific iron oxyhydroxide minerals precipitated in iron-silicate chemical gardens could vary depending on the experimental conditions, but could include green rust, a highly reactive mineral which may have driven relevant prebiotic reactions in alkaline hydrothermal systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Either way, many of the research challenges for the hypothesized role(s) of fougerite—dosed with various trace elements and anions—are similar. Such research addressing the submarine acid v. alkaline milieu calls for the further employment of tried-and-tested microfluidic and nano-crystallographic techniques [ 192 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 224 , 254 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 310 , 327 , 328 , 329 , 330 , 331 , 332 , 333 , 334 , 335 , 336 , 337 , 338 ]. We enumerate some possible developments from, expectations of, and tests for, the AVT below:…”
Section: What’s Next For the Avt?mentioning
confidence: 99%